Konstruksi City Branding Kota Pasuruan pada Instagram - Ilmia Sofia; Saifuddin Zuhri (Da'watuna: Journal of Communication and Islamic Broadcasting, 2022)
Branding is a term commonly used in the realm of marketing and advertising disciplines. Oneof the most common branding activities carried out is city branding activities. Many of each region carry out City Branding, one of which is Pasuruan City. This study aims to find out how Pasuruan City Branding contained in the content of @madinahvanjava Instagram account. The research method used is a qualitative type using Content Analysis and categorizing into 10 categories of city branding on Instagram according to (Choi et al., 2007). Hasil from this study, it can be concluded that the results of city branding construction on instagram account content @madinahvanjava within a period of 5 months, namely January-May 2022, can only be classified into 6 categories out of 10 categories that should be. uploads displayed by Instagram accounts @madinahvanjava less than optimal in membranding cities through Instagram social media. It is evident from the photos and videos uploaded that it favors the personal branding of the Mayor of Pasuruan than the display of the city branding of Pasuruan City. The strategy that should be used on @madinahvanjava Instagram account is to focus on posts related to city branding that provide information about Pasuruan City and not focus on the image of the Mayor. Keywords: City Branding, Branding, Content Analysis, Instagram Content